Determination of Job Satisfaction and Employee Loyalty: Analysis of Work Life Balance and Work Environment at PT WSI - Wirawan Widjanarko; Christophorus Indra Wahyu Putra; Kardinah Indrianna Meutia; Hasanuddin Hasanuddin; Rosalina Siagian; Mohamad Sobari; Gerry Juan Carlos (Dinasti Publisher, 2024)
Article Determining Job Satisfaction and Employee Loyalty: Analysis of Work Life Balance and Work Environment at PT WSI. The purpose of writing this article is to determine the influence of work life balance and work environment on job satisfaction and employee loyalty at PT WSI. The research method used is descriptive quantitative. The analytical tool used in this research is SEM SmartPLS 4.0. The sampling technique uses simple random sampling. The data used in this research is primary data. The population in this study was 194 respondents, with a research sample of 100 respondents, obtained from a questionnaire filled out by PT WSI employees. The tests carried out in this research are Validity Test, Reliability Test, Inner Model, Outer Model and Hypothesis Test. The results of this article are: 1) Work life balance has a significant effect on Job Satisfaction; 2) The work environment has a significant effect on Job Satisfaction; 3) Work life balance has no effect and is not significant on employee loyalty; 4) The work environment has a significant effect on employee loyalty; and 5) Job satisfaction has a significant effect on employee loyalty.